FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN RUMAH DI KOTA BATAM - Ronny Firdiansyah Arief (Universitas Lambung Mangkurat, 2022)
This study intends to analysis the factors that influence consumers in the city of Batam in their decision to buy a house. The factors are attributes of the house, location, surrounding environment, and house prices. Samples were taken from 377 respondents who are home owners/occupants in the city of Batam and statistical analysis using SPSS version 24. Environmental factors have the most significant influence on home buying decisions, followed by house attributes and housing locations. While the price factor according to the results of data processing carried out, the data is not reliable so that its influence cannot be analyzed.